Alternativas para la mitigación de asentamientos diferenciales en el edificio Av. 100 de la ciudad de Bogotá causados por la construcción de edificaciones vecinas. (2022)
Within this document an existing problematic is described, the building known as Av 100 locate in Bogotá, building’s bad condition due to differential settlements, related to the public works close to the building, To develop this project a descriptive research about the issue will be done and some alternatives to relief the differential settlements at Av 100 building, which will be developed by elaborating a comparison of geotechnical behavior for differential settlements problems, a historical description of structure foundations of buildings near by other buildings with differential settlements according to the structural methods of the time, and a comparative description of the stablished relief alternatives for Av 100 building. The current investigation was developed by researching and consulting different sources to generate a qualitative, informative and critical analysis, in order to expose the building’s problematic currently studied and stablish the possible alternatives which may be efficient to relief the differential settlements of the building